2021
DOI: 10.3390/cancers13122897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Thoracic Oncology Surgery in Spain: A Spanish Thoracic Surgery Society (SECT) Survey

Abstract: After the first wave of COVID-19, the Spanish Society of Thoracic Surgeons (SECT) surveyed its members to assess the impact of the pandemic on thoracic oncology surgery in Spain. In May 2020, all SECT members were invited to complete an online, 40-item, multiple choice questionnaire. The questionnaire was developed by the SECT Scientific Committee and sent via email. The overall response rate was 19.2%. The respondents answered at least 91.5% of the items, with only one exception (a question about residents). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(34 reference statements)
1
14
0
2
Order By: Relevance
“…Our institution benefitted from a novel triaging system that may limit the generalizability of this work, similar to other strategies reported ( 8 , 9 ). The system was developed to ensure timely delivery of care to our patients based on clinical stage, neoadjuvant treatment status, and need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our institution benefitted from a novel triaging system that may limit the generalizability of this work, similar to other strategies reported ( 8 , 9 ). The system was developed to ensure timely delivery of care to our patients based on clinical stage, neoadjuvant treatment status, and need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic revealed the needs for more information and guidance for changes in existing practice among lung cancer specialists including thoracic surgeons [ 16 ]. Many institutions have changed the treatment plan in order to minimize the risk of patient exposure, in accordance with recommendations of certain expert groups [ 17 , 18 , 19 , 20 , 21 , 22 ]. The consensus was that select treatment is still possible in a 28-day period.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Quebec Ministry’s report, very few patients had a cancer surgery within 0–56 days, while a greater proportion of cases were waiting for surgery more than 56 days. Participants of the Spanish Thoracic Society study also reported a decrease in surgical resection and prolonged wait time for surgery with a mean time exciding one month [ 20 ]. The majority of our patients receiving radiation therapy were treated within the recommended wait time.…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey of the Spanish Society of Thoracic Surgery a reduction by 95.7% of surgical procedures was observed (9). These data were confirmed by a survey of the European Society of Thoracic Surgeons (ESTS), that showed a delay of surgical procedures in 89% of the centers.…”
mentioning
confidence: 74%